Using smartphones to extend interaction beyond the EFL classroom. Issue 4 (3rd May 2020) - Wrigglesworth, Jonathan
Abstract: Successful second language learning can be seen as occurring in two arenas; the exposure and learning which occurs, under the guidance of a formal education setting, under the guidance of an instructor and that which occurs informally, under the guidance of the learner or incidentally as the learner pursues other activities. As smartphones have become more available and affordable, educators and learners have looked at the potential these devices offer to extend language learning opportunities beyond the classroom. This study looked at how university English language learners engaged in student-led communicative tasks on an Multimedia Messaging Systems platform accessed through their smartphones. In designing the study, I took an interactionist perspective and used sociocultural theory as an analytical tool in my analysis. The results showed that learners successfully engaged in these tasks and that they found them useful as language learning activities. Although there was a low level of negotiation of meaning between peers, the participants were heavily involved in using affordances on their smartphones to help them engage in the tasks.